PENGARUHÃÂ INFORMASIÃÂ KEWIRASWASTAANÃÂ ÃÂ TERHADAPÃÂ MINATÃÂ MAHASISWAÃÂ UNTUKÃÂ BERWIRASWASTAÃÂ ÃÂ - MuslihÃƒÂ‚Ã‚Â , Muhamad; KhumaediÃƒÂ‚Ã‚Â ÃƒÂ‚Ã‚Â , M.ÃƒÂ‚Ã‚Â ; AlÃƒÂ‚Ã‚Â JananÃƒÂ‚Ã‚Â , Dony HidayatÃƒÂ‚Ã‚Â (Jurnal Pendidikan Teknik Mesin, 2008)
TujuanÃÂ penelitianÃÂ iniÃÂ adalahÃÂ untukÃÂ mengetahuiÃÂ tingkatÃÂ informasiÃÂ kewiraswastaan,ÃÂ mengukurÃÂ minatÃÂ mahasiswaÃÂ dalamÃÂ berwiraswasta,ÃÂ mengujiÃÂ pengaruhÃÂ  informasiÃÂ kewiraswastaanÃÂ terhadapÃÂ minatÃÂ berwiraswasta,ÃÂ sertaÃÂ mengetahuiÃÂ  pengaruhÃÂ  informasiÃÂ  kewiraswastaanÃÂ  terhadapÃÂ  minatÃÂ  berwiraswastaÃÂ  padaÃÂ  mahasiswaÃÂ  PendidikanÃÂ TeknikÃÂ Mesin,ÃÂ FakultasÃÂ Teknik,ÃÂ UniversitasÃÂ NegeriÃÂ SemarangÃÂ angkatanÃÂ 2006.ÃÂ PenelitianÃÂ iniÃÂ mengunakanÃÂ metodeÃÂ survai,ÃÂ denganÃÂ populasiÃÂ 80ÃÂ orangÃÂ mahasiswa.ÃÂ HasilÃÂ analisisÃÂ deskriptifÃÂ menunjukkanÃÂ bahwaÃÂ minatÃÂ mahasiswaÃÂ untukÃÂ berwiraswastaÃÂ  tergolongÃÂ  baik.ÃÂ TingkatÃÂ  informasiÃÂ  kewiraswastaanÃÂ  yangÃÂ  diterimaÃÂ mahasiswaÃÂ  jugaÃÂ  tergolongÃÂ  baik.ÃÂ HasilÃÂ analisisÃÂ regresiÃÂ menunjukkanÃÂ besarnyaÃÂ pengaruhÃÂ  informasiÃÂ kewiraswastaanÃÂ  terhadapÃÂ minatÃÂ berwiraswastaÃÂ sebesarÃÂ  49,28%.ÃÂ HendaknyaÃÂ  semuaÃÂ  pihakÃÂ  dapatÃÂ memberikanÃÂ  informasiÃÂ  kewiraswastaanÃÂ  kepadaÃÂ mahasiswaÃÂ  danÃÂ mahasiswaÃÂ jugaÃÂ aktifÃÂ mencariÃÂ informasiÃÂ tersebutÃÂ sehinggaÃÂ dapatÃÂ menumbuhkanÃÂ  jiwaÃÂ entrepreneurshipÃÂ padaÃÂ diriÃÂ setiapÃÂ mahasiswa. ÃÂ  KataÃÂ kunci:ÃÂ informasiÃÂ kewiraswastaan,ÃÂ minatÃÂ berwiraswastaTheÃÂ objectivesÃÂ ofÃÂ  thisÃÂ researchÃÂ areÃÂ  toÃÂ knowÃÂ theÃÂ entrepreneurialÃÂ  informationÃÂ  level,ÃÂ toÃÂ measureÃÂ studentsÃ¢â¬â¢ÃÂ interestÃÂ  inÃÂ beingÃÂ entrepreneurs,ÃÂ  toÃÂ  testÃÂ  theÃÂ effectÃÂ ofÃÂ entrepreneurialÃÂ  informationÃÂ  towardÃÂ studentsÃ¢â¬â¢ÃÂ  interestÃÂ  toÃÂ beÃÂ entrepreneurs,ÃÂ andÃÂ toÃÂ identifyÃÂ theÃÂ effectÃÂ ofÃÂ entrepreneurialÃÂ informationÃÂ towardÃÂ studentsÃÂ atÃÂ echanicalÃÂ EngineeringÃÂ  EducationÃÂ  FacultyÃÂ  ofÃÂ  EngineeringÃÂ  SemarangÃÂ  StateÃÂ UniversityÃÂ  yearÃÂ  2006.ÃÂ ThisÃÂ  researchÃÂ  usedÃÂ  surveyÃÂ methodÃÂ withÃÂ populationÃÂ consistingÃÂ ofÃÂ 80ÃÂ students.ÃÂ TheÃÂ descriptiveÃÂ resultÃÂ showsÃÂ thatÃÂ studentsÃ¢â¬â¢interestÃÂ toÃÂ beÃÂ entrepreneursÃÂ isÃÂ inÃÂ goodÃÂ quality.ÃÂ TheÃÂ regressiveÃÂ analysisÃÂ resultÃÂ showsÃÂ thatÃÂ theÃÂ percentageÃÂ ofÃÂ entrepreneurialÃÂ informationÃÂ effectÃÂ towardÃÂ studentsÃ¢â¬â¢ÃÂ interestÃÂ inÃÂ beingÃÂ entrepreneursÃÂ isÃÂ 49,28%.ÃÂ ItÃÂ isÃÂ suggestedÃÂ thatÃÂ allÃÂ peopleÃÂ couldÃÂ explainÃÂ entrepreneurialÃÂ informationÃÂ toÃÂ students.ÃÂ InÃÂ turn,ÃÂ theÃÂ studentsÃÂ themselvesÃÂ shouldÃÂ beÃÂ activeÃÂ inÃÂ graspingÃÂ theÃÂ informationÃÂ soÃÂ theirÃÂ motivationÃÂ andÃÂ spiritÃÂ toÃÂ beÃÂ entrepreneursÃÂ willÃÂ grow. Keywords:ÃÂ entrepreneurialÃÂ information,ÃÂ interestÃÂ inÃÂ beingÃÂ entrepreneurs ÃÂ ÃÂ